Karakteristik Minyak Atsiri Daun Melaleuca leucadendra L. dari Empat Lokasi yang Berbeda Di Kabupaten Paser Kalimantan Timur - Agmi Bagus Kartiko; Enih Rosamah; Harlinda Kuspradini (Fakultas Kehutanan Universitas Mulawarman, 2021)
Cajuput oil, which comes from the Melaleuca, is one of the NTFPs that is widely used for various health or pharmaceutical products so that it is a product that is in great demand. This study aimed to measure the yield and analyze the physical properties of M. leucadendra L. essential oil which comes from Paser, East Kalimantan. Samples were taken from 4 different locations, namely Rantau Panjang, Jone, Padang Pangrapat and Pondong Baru. Essential oils were obtained from distillation process using the water and steam method. The physical characteristics of essential oils were analyzed including visual color and refractive index using a hand refractometer. The results of M. leucadendra L. oil distillation from 4 locations, namely Rantau Panjang, Jone, Padang Pangrapat and Pondong Baru. showed the various yields, among others, 0.030%, 0.066%, 0.104% and 0.031%. The color of the essential oil observed also varied from yellow to orange and the refractive index range obtained was 1,429-1,450. The results of this study have the potential as a new source of cajuput oil originating from East Kalimantan, however further research is needed to find out about the appropriate distillation technique in order to increase the yield of M. leucadendra essential oil.